The impact of multi‐organ transplant allocation priority on waitlisted kidney transplant candidates. Issue 6 (22nd November 2020) - Westphal, Scott G.; Langewisch, Eric D.; Robinson, Amanda M.; Wilk, Amber R.; Dong, Jianghu J.; Plumb, Troy J.; Mullane, Ryan; Merani, Shaheed; Hoffman, Arika L.; Maskin, Alexander; Miles, Clifford D.
Abstract: Kidney‐alone transplant (KAT) candidates may be disadvantaged by the allocation priority given to multi‐organ transplant (MOT) candidates. This study identified potential KAT candidates not receiving a given kidney offer due to its allocation for MOT. Using the Organ Procurement and Transplant Network (OPTN) database, we identified deceased donors from 2002 to 2017 who had one kidney allocated for MOT and the other kidney allocated for KAT or simultaneous pancreas–kidney transplant (SPK) ( n  = 7, 378). Potential transplant recipient data were used to identify the "next‐sequential KAT candidate" who would have received a given kidney offer had it not been allocated to a higher prioritized MOT candidate. In this analysis, next‐sequential KAT candidates were younger ( p  < .001), more likely to be racial/ethnic minorities ( p  < .001), and more highly sensitized than MOT recipients ( p  < .001). A total of 2, 113 (28.6%) next‐sequential KAT candidates subsequently either died or were removed from the waiting list without receiving a transplant. In a multivariable model, despite adjacent position on the kidney match‐run, mortality risk was significantly higher for next‐sequential KAT candidates compared to KAT/SPK recipients (hazard ratio 1.55, 95% confidence interval 1.44, 1.66). These results highlight implications of MOT allocation prioritization, and potential consequences to KAT candidates prioritized below MOT candidates. Abstract : This study assesses characteristics and subsequent outcomes of kidney‐alone transplant candidates who were next in sequence on a given kidney match run, but did not receive a potential organ offer due to its allocation for multi‐organ transplantation. See an editorial from Schold and Mohan on page 2004 .